Yyteistä uuteen alkuun toimittajien kertomuksia mediatyön murroksesta - Harju, Auli (Tampere University Press, 2017)
"Towards New Beginnings: Journalists' Descriptions about Ruptures in Media Work This volume reveals a previously untold view on changes in media work in Finland. Finnish journalists relate their experiences of being made redundant or deciding to resign, and their views on their profession in a time of flux. The data are based on telephone surveys, in-depth interviews and journalists' written accounts. Journalists are riddled with insecurity about their future. They feel they have borne the brunt of misplaced investments and the economic conjuncture, and their work motivation and creativity have suffered due to recurring layoffs in newsrooms. Support from employment authorities for finding a new job has also been practically non-existent, and coping with a career change has generated further stress and insecurity. However, journalists who have found new employment typically feel more comfortable in these jobs than in their former work. Career shifters have also been able to make use of their journalistic skills in their new jobs and identify themselves as journalists. The authors are from the Research Centre for Journalism, Media and Communication (COMET) at the University of Tampere, Finland. The study was funded by the Finnish Work Environment Fund and the Foundation for Promoting Journalistic Culture (JOKES). "